Peran Orang Tua Dalam Perkembangan Sosial Emosional Anak Usia Dini - Fitria Ningsih; Indah Nurita Sitompul; Khadijah Khadijah; Homsani Nasution (Journal on Education, 2025)
Parental involvement holds a vital position, particularly in fostering the social and emotional growth of young children. This situation arises because a number of parents have not yet fully recognized the significance of nurturing social and emotional aspects during early development. This research is designed to explore and portray the various roles undertaken by parents in supporting children’s social and emotional development. The study employs a qualitative research design, utilizing data collection methods such as observation, in-depth interviews, and documentation. The findings reveal that parents contribute substantially to early childhood social and emotional development by acting as educators, mentors, and facilitators.